Dog days - English, Karen (English, Karen. Carver chronicles., 2013)
Gavin wants to make a good impression at Carver Elementary, where no one knows he excels at soccer and skateboarding, but an annoying big sister, a bully, and his great aunt's Pomeranian are not helping.